1998
DOI: 10.1590/s0034-71081998000400006
|View full text |Cite
|
Sign up to set email alerts
|

Seleção de hábitat em duas espécies de jararaca (Bothrops moojeni Hoge e B. neuwiedi Wagler) (Serpentes, Viperidae)

Abstract: Habitat selection by two lancehead species (Bothrops moojeniHoge and B. neuwiedi Wagler) (Serpentes, Viperidae)Our data regarding the use of the habitat by Bothrops moojeni and B. neuwiedi (Serpentes, Viperidae) was obtained from information related to specimens donated to the Jardim Zoológico de Brasília, Universidade de Brasília, Jardim Botânico do Distrito Federal, and also from a half-captivity experiment. The results show a strong segregation of habitat between both species, with B. neuwiedi largely restr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 14 publications
0
8
0
1
Order By: Relevance
“…In South America, with the exception of a few studies (e.g., Duellman, 1978;Borges and Araú jo, 1998;Marques and Puorto, 1998), little is known about the biology of snakes (Vitt, 1980). This is especially true of aquatic species, which generally are more restricted to tropical climates (Greene, 1997).…”
mentioning
confidence: 99%
“…In South America, with the exception of a few studies (e.g., Duellman, 1978;Borges and Araú jo, 1998;Marques and Puorto, 1998), little is known about the biology of snakes (Vitt, 1980). This is especially true of aquatic species, which generally are more restricted to tropical climates (Greene, 1997).…”
mentioning
confidence: 99%
“…moojeni is commonly found in central and southeastern Brazil, being most prolific in the savanna('Cerrado') (Borges and Araujo, 1998;FUNASA, 2001). Studies have revealed that B. moojeni venom exhibits high proteolytic activity and low hemorrhagic action, with high PLA 2 levels and coagulant properties (Assakura et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…All specimens have a microchip under their skin. To facilitate identification, the tail of each animal was painted with nail polish of a different color (6).…”
Section: Methodsmentioning
confidence: 99%
“…Although these techniques are more commonly used in the field, other methods are employed in semi-extensive breeding for individual identification (6). Semiextensive breeding can provide new information on snakes' habits such as segregation, habitat use, and thermoregulation (2,6,7).…”
Section: Introductionmentioning
confidence: 99%